Lecturers' and Students' Perspectives on the Importance of Sustainability Accounting in the Accounting Learning Curriculum - Suminar, Lintang; Utami, Helianti; Restuningdiah, Nurika (Journal of Educational Analytics, 2024)
The purpose of this article is to explore the perspectives of lecturers and students as actors in learning sustainability accounting and Sustainability Reporting (SR) courses and whether these courses can prepare them for employment opportunities in the sustainability field. Using a qualitative research method with a phenomenological approach, it was found that in learning sustainability accounting and SR, the most important thing is how students have the awareness to be sensitive to social, economic, and environmental issues. In its implementation, it is appropriate to be applied as an elective course, although it does not rule out the possibility of this course being made a compulsory course and curriculum redesign, and with the implementation of this course at least students have an initial understanding of the concept of sustainability accounting and principles regarding the preparation of SR, although they cannot fill job opportunities in the field of sustainability.